Preparation method of super-large blue-light perovskite nanosheet with high fluorescence quantum yield

By preparing ultra-large blue light perovskite nanosheets with high fluorescence quantum yield, the problems of low fluorescence quantum yield and poor stability of existing blue light nanomaterials have been solved, and efficient luminescence and stability are achieved. It is suitable for high-performance optoelectronic devices and biology Medical applications.

CN119432376APending Publication Date: 2025-02-14INST OF PHYSICS HENAN ACAD OF SCI +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411363200.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing blue light nanomaterials have low fluorescence quantum yield and small size, resulting in low luminescence efficiency and poor stability, which cannot meet the needs of high-performance optoelectronic devices and advanced biomedical applications.

Method used

A high fluorescent quantum yield ultra-large blue light perovskite nanosheets are prepared by preparing precursors A and B, the original solution of nanosheets is synthesized, and the surface defects of nanosheets are passivated, and purified by multiple centrifugation and dispersion treatments. , blue light perovskite nanosheets with high fluorescent quantum yield were obtained.

Benefits of technology

It improves the structural stability and resistance to external interference, enhances the modification of surface properties, and can accurately regulate the size and thickness of nanosheets, significantly improving the luminous efficiency and display quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432376A_ABST
    Figure CN119432376A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-fluorescence quantum yield ultra-large blue light perovskite nanosheet. The preparation method comprises the following steps: S1, preparing a precursor solution A; s2, preparing a precursor solution B; s3, synthesizing a perovskite nanosheet; s4, passivating surface defects of the nanosheets; and S5, purifying the perovskite nanosheet. The large-size planar structure of the super-large perovskite nanosheet enables the super-large perovskite nanosheet to have better optical performance stability in some applications. Higher predictability and stability are shown in the aspects of optical and electrical properties. A crystal structure of a quantum dot is relatively complex, and due to the fact that the crystal structure is small in size, the surface effect and the quantum confinement effect are more remarkable, instability of the crystal structure and uncertainty of performance are possibly caused. The oversized perovskite nanosheet can reduce the adverse effects to a certain extent, and provides more reliable performance. The surface of the oversized perovskite nanosheet is relatively flat, and surface modification and functionalization are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nano functional materials and display lighting, and in particular to a method for preparing a high fluorescence quantum yield ultra-large blue light perovskite nanosheet. Background Art

[0002] Blue light materials, as an indispensable key element in the field of modern science and technology, play a vital role in many cutting-edge fields. In the field of light-emitting diodes (LEDs), it is one of the core elements to achieve efficient energy-saving lighting and high-definition display; in display technology, the clever combination of blue light and other colors of light can present colorful, lifelike and clear full-color images, bringing people a shocking visual experience; in the field of biological imaging, blue light is like a magical "probe" that can penetrate deep into cells and accurately image cell structure and function, providing a powerful tool for disease diagnosis and medical research; and in the field of photocatalysis, blue light plays an important role in activating catalysts, promoting the efficient progress of chemical reactions, and providing a new way to solve energy and environmental problems.

[0003] However, existing blue light nanomaterials have many unsatisfactory performances. Traditional blue light nanomaterials often have low fluorescence quantum yields, which is like a funnel. A large amount of energy is quietly lost during the light-emitting process, resulting in a significant reduction in luminous efficiency and unable to meet the growing demand for high performance. At the same time, their small size limits their application in optoelectronic devices to a certain extent. For example, in display screens, they may affect the clarity and brightness uniformity of the image. In addition, poor stability is also a problem that needs to be solved urgently. These materials are easily disturbed by external environmental factors (such as changes in light intensity, temperature fluctuations, humidity, etc.), resulting in performance degradation, shortening their service life and increasing their use costs.

[0004] In view of this, in order to meet the urgent needs of modern science and technology for high-performance optoelectronic devices and advanced biomedical applications, the development of a method for preparing blue light nanosheets with high fluorescence quantum yield, ultra-large size and good stability has become the focus of common attention in the scientific and industrial communities. The birth of this new material is not only expected to greatly improve the luminous efficiency and display quality of optoelectronic devices, making them stand out in the fiercely competitive market, but also to bring more sensitive and accurate detection and diagnosis methods to research and clinical applications in the biomedical field, and contribute to the development of human health. Summary of the invention

[0005] The present invention provides a method for preparing a perovskite nanosheet with high fluorescence quantum yield and ultra-large blue light, and the specific steps are as follows

[0006] S1: preparing precursor solution A;

[0007] S2: preparing precursor solution B;

[0008] S3: original solution for synthesizing nanosheets;

[0009] S4: passivation of nanosheet surface defects;

[0010] S5: Purification of perovskite blue light nanosheets.

[0011] Furthermore, step S1 is specifically as follows:

[0012] The A salt, the organic ligand and the non-coordinating solvent are fully mixed, raised to a certain temperature T1, and stirred for a predetermined time, thereby successfully obtaining a clear and transparent cesium precursor solution A;

[0013] Furthermore, step S2 is specifically as follows:

[0014] The lead halide and the non-coordinating solvent are mixed, and then vacuumed. The mixed solution is then heated to a certain temperature T2, and then an organic anion ligand and an organic cation ligand are added, and the temperature is raised to a certain temperature T3. The mixture is stirred for a certain period of time until the solution is clear and transparent, and then a precursor solution B is obtained.

[0015] Furthermore, step S3 is specifically as follows:

[0016] Precursor solution B is heated to temperature T4 and stirred at a certain rate, and then precursor solution A is injected into precursor solution B at a certain rate through a peristaltic pump, reacted for a certain time, and then the solution is quickly cooled to room temperature to obtain the original solution of blue light nanosheets;

[0017] Furthermore, step S4 is specifically as follows:

[0018] Alkaline earth metal halide, oleic acid and octadecene are mixed, stirred for a certain time at a certain temperature T5 to obtain a clear solution C, and then a certain amount of solution C and a certain amount of sulfonic acid ligand are added to the original solution of blue light nanosheets, stirred for a certain time at a certain temperature T6 to obtain a blue light nanosheet solution with high fluorescence quantum yield;

[0019] Furthermore, step S5 is specifically as follows:

[0020] A predetermined amount of anti-solvent is added to the solution prepared in S4 for centrifugation. Subsequently, the obtained precipitate is added to the solvent for dispersion again, and the above steps are repeated multiple times to completely remove the reaction waste generated during the synthesis of the nanosheets, and finally a clean blue light perovskite nanosheet with high fluorescence quantum yield is successfully obtained.

[0021] Further, in step S1,

[0022] Salt A is one or more of cesium carbonate, cesium nitrate, cesium vanadate, cesium oxalate, cesium chromate, cesium permanganate, cesium dichromate, cesium borate, cesium silicate, cesium sulfite, cesium tungstate, cesium molybdate, cesium dihydrogen phosphate, cesium oleate, cesium propionate, cesium butyrate, cesium citrate, cesium sulfate and cesium tartrate; the organic ligand is one or more of octanoic acid, oleic acid, stearic acid, capric acid and trioctylphosphine oxide; the non-coordinating solvent is octadecene. The temperature T1 is 90-150°C; the stirring time is 30-200min; the stirring speed is 200-800rpm. The concentration of precursor solution A is 0.0108-0.8235g / mL.

[0023] Further, in step S2,

[0024] The lead halide is one or both of lead bromide and lead chloride; the non-coordinating solvent is octadecene; the organic cationic ligand is one or more of oleic acid, stearic acid, oxalic acid, mercaptopropionic acid, dodecanethiol, thioglycolic acid, undecylenic acid, octanoic acid, and trioctylphosphine oxide; the organic anionic ligand may be, but is not limited to, one or more of oleylamine, dodecylamine, hexadecylamine, trioctylamine, tributylamine, trioctylphosphine, and octylamine; the vacuum degree is 0.6-50 Pa, and the temperature T2 is 60-130° C.; the volume ratio of the organic anionic ligand to the organic cationic ligand is 0.2-1.5:1, and the volume ratio of the organic anionic ligand to the non-coordinating solvent is 0.23-1.8:1; the temperature T3 is 140-250° C., the stirring time is 20-150 min, and the concentration of the precursor solution B is 0.0032-0.9732 g / mL.

[0025] Further, in step S3,

[0026] The temperature T4 is 130-220°C; the stirring speed is 300-1200rpm; the peristaltic pump flow range is 0.002-32ml / h; the reaction time is 20min-48h;

[0027] Further, in step S4,

[0028] The alkaline earth metal halide is one or more of calcium chloride, magnesium chloride, strontium chloride, barium chloride, calcium bromide, magnesium bromide, strontium bromide and barium bromide; the temperature T5 is 60-150°C; the stirring time at the temperature T5 is 30-300 minutes; the sulfonic acid ligand is sodium benzenesulfonate, p-toluenesulfonic acid, 2-naphthalenesulfonic acid, 3-amino-4-methylbenzenesulfonic acid, aminomethanesulfonic acid, 2-amino-3,5-dimethylbenzenesulfonic acid, aminomethanesulfonic acid, 4-dodecylbenzenesulfonic acid, 2-sulfonatoterephthalic acid , isophthalic acid-5-sulfonic acid, 1,3,5-benzenetrisulfonic acid, 4-chlorobenzenesulfonic acid, 2-carboxybenzenesulfonic acid, 3-carboxybenzenesulfonic acid, 4-aminobenzenesulfonic acid, 4-sulfonylbenzoic acid and 1-naphthalenesulfonic acid or more; temperature T6 is room temperature to 180°C; stirring time at temperature T6 is 20 to 240 min; weight ratio of alkaline earth metal halide to sulfonic acid ligand is 0.25 to 2.3:1; weight ratio of alkaline earth metal halide to lead halide is 0.02 to 0.65:1.

[0029] Further, in step S5,

[0030] The volume ratio of the antisolvent to the solvent is 0.2-2:1, and the volume ratio of the antisolvent to the blue light nanosheet solution is 0.5-1.8:1; the antisolvent is ethyl acetate; the solvent is one of toluene, n-hexane, cyclohexane, benzene, and octane; the centrifugal speed is 800rpm-10000rpm; and the centrifugal time is 3min-30min.

[0031] Compared with the prior art, this patent application has the following beneficial effects:

[0032] 1. Enhanced structural stability: The structure of nanosheets is relatively more stable. Traditional perovskite quantum dots are prone to agglomeration and Ostwald ripening due to their high surface energy and small size, resulting in poor stability. The larger planar structure of perovskite nanosheets reduces the impact of these unstable factors to a certain extent. For example, during long-term use, perovskite nanosheets can better maintain their optical properties and structural integrity.

[0033] 2. Improved resistance to external interference: Perovskite nanosheets show better stability to external factors such as light, heat, and air. In contrast, traditional monodisperse perovskite quantum dots are easily photodegraded by light, easily oxidized in the air, and sensitive to heat. They may experience performance degradation or even structural damage at higher temperatures. Perovskite nanosheets have a stronger resistance to these external interference factors due to their relatively stable structure and surface characteristics. For example, in some outdoor or complex environment applications, perovskite nanosheets have more obvious advantages.

[0034] 3. Modifiable surface properties: The surface of perovskite nanosheets is easier to chemically modify, and its surface properties can be changed by introducing different ligands or functional groups, thereby adjusting its interaction with the surrounding environment and optical properties. This surface modifiability provides more possibilities for further optimizing the performance of perovskite nanosheets and expanding their application range, such as improving their dispersibility in specific solvents or matrices and enhancing their compatibility with other materials through surface modification.

[0035] 4. Size and thickness can be precisely controlled: By changing the synthesis conditions, the size and thickness of perovskite nanosheets can be more accurately controlled, thereby achieving fine adjustment of their optical properties. For example, perovskite nanosheets with specific emission wavelengths can be synthesized according to different application requirements to meet the precise control of different colors of light, which is of great value in the fields of multi-color display and optical communication. However, traditional monodisperse perovskite quantum dots may be relatively limited in the accuracy and range of size control. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Mg:CsPbBr in a method for preparing a high fluorescence quantum yield ultra-large blue light perovskite nanosheet according to the present invention 3-x Cl x Fluorescence quantum yield of ultra-large blue nanosheets;

[0037] Figure 2 Mg:CsPbBr in a method for preparing a high fluorescence quantum yield ultra-large blue light perovskite nanosheet according to the present invention 3-x Cl x Transmission electron microscope morphology of ultra-large blue light nanosheets;

[0038] Figure 3 Mg:CsPbBr in a method for preparing a high fluorescence quantum yield ultra-large blue light perovskite nanosheet according to the present invention 3-x Cl x A magnified transmission electron microscope image of the ultra-large blue nanosheet;

[0039] Figure 4 Mg:CsPbBr in a method for preparing a high fluorescence quantum yield ultra-large blue light perovskite nanosheet according to the present invention 3-x Cl x Fluorescence image of ultra-large blue nanosheets;

[0040] Figure 5 Mg:CsPbBr in a method for preparing a high fluorescence quantum yield ultra-large blue light perovskite nanosheet according to the present invention 3-x Cl x Absorption map of the ultra-large blue light nanosheet. DETAILED DESCRIPTION

[0041] The present invention will be further described below through specific embodiments in conjunction with the accompanying drawings.

[0042] Example 1

[0043] A method for preparing a perovskite nanosheet with high fluorescence quantum yield and ultra-large blue light comprises the following steps:

[0044] S1: Prepare precursor solution A

[0045] 0.45 g of cesium carbonate, 1.5 mL of oleic acid, 0.7 mL of octanoic acid and 10 mL of octadecene were fully mixed, heated to 130°C, stirred for 90 min at a stirring speed of 500 rpm, and a clear and transparent cesium precursor solution with a concentration of 0.0368 g / mL was obtained;

[0046] S2: Prepare precursor solution B

[0047] 0.105 g of lead chloride, 0.032 g of lead bromide and 10 mL of octadecene were mixed, evacuated to 20 Pa, heated to 120° C., and then 1.5 mL of oleic acid, 1.5 mL of oleylamine and 2 mL of trioctylphosphine were added to the solution, and then the temperature was raised to 170° C. and stirred at this temperature for 30 min to obtain a clear and transparent lead halide precursor solution with a concentration of 0.0091 g / mL;

[0048] S3: Original solution for synthesizing nanosheets

[0049] Precursor solution B was heated to 170°C and stirred at 300 rpm, and then precursor solution A was injected into precursor solution B at a rate of 2.4 mL / h through a peristaltic pump, reacted for 20 minutes, and then the solution was quickly cooled to room temperature to obtain the original solution of blue light nanosheets;

[0050] S4: Passivation of nanosheet surface defects

[0051] 0.1 g of magnesium chloride, 2 mL of oleic acid and 10 mL of octadecene were mixed and stirred at 140 °C for 30 min to obtain a clear solution C. Then 2 mL of solution C and 0.15 g of 2-carboxybenzenesulfonic acid were added to the blue light nanosheets and stirred at 140 °C for 120 min to obtain blue light Mg:CsPbBr with high fluorescence quantum yield. 3-x Cl x Nanosheet solution;

[0052] S5: Purification of Nanosheets

[0053] Take 5 mL of the solution prepared by S4, add 10 mL of ethyl acetate to it, and centrifuge at a speed of 5000 rpm for 5 min. Then, add the obtained precipitate to n-hexane for dispersion again; add ethyl acetate to the solution again, then centrifuge, and then add the obtained precipitate to n-hexane for dispersion again, and finally successfully obtain clean blue light Mg:CsPbBr 3-x Cl x Nanosheets.

[0054] First, the fluorescence quantum yield of the nanosheets was characterized. It was found that the fluorescence quantum yield of the initially synthesized blue light nanosheets was 67.1%. After modification with magnesium chloride and 2-carboxybenzenesulfonic acid, the fluorescence quantum yield increased to 93.6% ( Figure 1 ). Then, CsPbBr 1-x Cl x The blue light nanosheets were characterized by TEM, and it was found that the nanosheets were square with a side length of 200 to 500 nm ( Figure 2 ,3). Through fluorescence spectroscopy characterization, it was found that Mg:CsPbBr 3-x Cl x The fluorescence peak of the nanosheet is at 456nm, and the half-peak width is 35nm ( Figure 4 ), showing that Mg:CsPbBr 3-x Cl x Nanosheets can be used as excellent blue light illumination or display materials, with absorption peaks at 410nm and 425nm ( Figure 5 ).

[0055] Example 2

[0056] A method for preparing a perovskite nanosheet with high fluorescence quantum yield and ultra-large blue light comprises the following steps:

[0057] S1: Prepare precursor solution A

[0058] 0.25 g of cesium carbonate, 0.15 g of cesium nitrate, 1.5 mL of oleic acid, 0.9 mL of octanoic acid and 10 mL of octadecene were fully mixed, heated to 140°C, stirred for 120 min at a stirring speed of 500 rpm, and a clear and transparent cesium precursor solution with a concentration of 0.0322 g / mL was obtained;

[0059] S2: Prepare precursor solution B

[0060] 0.138 g of lead bromide was mixed with 10 mL of octadecene, and the mixture was evacuated to 20 Pa, and the temperature was raised to 120° C. Then, 1.5 mL of oleic acid and 1.5 mL of oleylamine were added to the solution, and the temperature was subsequently raised to 170° C. and stirred at this temperature for 30 min to obtain a clear and transparent lead halide precursor solution with a concentration of 0.0106 g / mL.

[0061] S3: Original solution for synthesizing nanosheets

[0062] The precursor solution B was heated to a temperature of 130°C and stirred at a speed of 500 rpm, and then the precursor solution A was injected into the precursor solution B at a rate of 1.8 mL / h through a peristaltic pump, and the reaction was carried out for 40 minutes, and then the solution was quickly cooled to room temperature to obtain the original solution of CsPbBr3 perovskite nanosheets;

[0063] S4: Passivation of nanosheet surface defects

[0064] 0.1 g of calcium chloride, 2 mL of oleic acid and 10 mL of octadecene were mixed and reacted at 140°C for 30 min to obtain a clear solution C. Then 2 mL of solution C and 0.3 g of 2-carboxybenzenesulfonic acid were added to the original solution of perovskite nanosheets and stirred at 140°C for 120 min to obtain a blue light Ca:CsPbBr3 nanosheet solution with high fluorescence quantum yield.

[0065] S5: Purification of Nanosheets

[0066] Take 5 mL of the solution prepared by S4, add 10 mL of ethyl acetate thereto, and centrifuge at a speed of 5000 rpm for 5 min. Then, add the obtained precipitate to n-hexane for dispersion again, add ethyl acetate to the solution again, and then centrifuge, then add the obtained precipitate to n-hexane for dispersion again, and finally successfully obtain clean blue light Ca:CsPbBr3 nanosheets.

[0067] Example 3

[0068] A method for preparing a perovskite nanosheet with high fluorescence quantum yield and ultra-large blue light comprises the following steps:

[0069] S1: Prepare precursor solution A

[0070] 0.35 g of cesium nitrate, 1.5 mL of oleic acid, 0.5 mL of octanoic acid and 10 mL of octadecene were fully mixed, heated to 150° C., stirred for 150 min at a stirring speed of 500 rpm, and a clear and transparent cesium precursor solution with a concentration of 0.0291 g / mL was obtained;

[0071] S2: Prepare precursor solution B

[0072] 0.1408 g of lead chloride was mixed with 10 mL of octadecene, and the mixture was evacuated to 20 Pa and heated to 120° C. Then, 1 mL of oleic acid, 0.8 mL of oleylamine and 2.4 mL of trioctylphosphine were added to the solution, and the temperature was then raised to 180° C. The mixture was stirred at this temperature for 60 min to obtain a clear and transparent lead chloride precursor solution with a concentration of 0.0099 g / mL.

[0073] S3: Original solution for synthesizing nanosheets

[0074] Precursor solution B was heated to 200°C and stirred at 800 rpm, and then precursor solution A was injected into precursor solution B at a rate of 3.6 mL / h through a peristaltic pump, reacted for 60 minutes, and then the solution was quickly cooled to room temperature to obtain the original solution of CsPbCl3 perovskite nanosheets;

[0075] S4: Passivation of nanosheet surface defects

[0076] 0.1 g of strontium chloride, 3 mL of oleic acid and 8 mL of octadecene were mixed and reacted at 120°C for 30 min to obtain a clear solution C. Then 2 mL of solution C and 0.2 g of 4-aminobenzenesulfonic acid were added to the original solution of perovskite nanosheets and stirred at 120°C for 240 min to obtain a blue light Sr:CsPbCl3 nanosheet solution with high fluorescence quantum yield.

[0077] S5: Purification of Nanosheets

[0078] Take 2.4 mL of the solution prepared by S4, add 5 mL of ethyl acetate thereto, and centrifuge at a speed of 6000 rpm for 5 min. Then, add the obtained precipitate to n-hexane for dispersion again, add ethyl acetate to the solution again, and then centrifuge, then add the obtained precipitate to n-hexane for dispersion again, and finally successfully obtain clean blue light Sr:CsPbCl3 nanosheets.

Claims

1. A method for preparing a high fluorescence quantum yield ultra-large blue light perovskite nanosheet, characterized in that: The specific steps are as follows: S1: preparing precursor solution A; S2: preparing precursor solution B; S3: original solution for synthesizing nanosheets; S4: passivation of nanosheet surface defects; S5: Purification of perovskite blue light nanosheets.

Citation Information

Patent Citations

  • High-performance blue-light perovskite nanosheet and preparation method thereof

    CN118599532A